2015
DOI: 10.18632/oncotarget.5899
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response (DDR) and senescence: shuttled inflamma-miRNAs on the stage of inflamm-aging

Abstract: A major issue in aging research is how cellular phenomena affect aging at the systemic level. Emerging evidence suggests that DNA damage response (DDR) signaling is a key mechanism linking DNA damage accumulation, cell senescence, and organism aging. DDR activation in senescent cells promotes acquisition of a proinflammatory secretory phenotype (SASP), which in turn elicits DDR and SASP activation in neighboring cells, thereby creating a proinflammatory environment extending at the local and eventually the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 144 publications
2
109
1
4
Order By: Relevance
“…Although inflammation has been suggested to have a key role in T2DM development and progression, its molecular bases are still being investigated [4244]. Inflammaging - the age-related chronic state of low grade inflammation that modulates the aging process and promotes the development and progression of age-related diseases - is mainly sustained by protracted activation of the immune system and an increased burden of senescent cells with a secretory phenotype (SASP) [4546]. Support for the link between telomere length and systemic inflammation has recently been provided by the report that telomeric repeat-containing RNA (TERRA) is a component of extracellular inflammatory exosomes [47].…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammation has been suggested to have a key role in T2DM development and progression, its molecular bases are still being investigated [4244]. Inflammaging - the age-related chronic state of low grade inflammation that modulates the aging process and promotes the development and progression of age-related diseases - is mainly sustained by protracted activation of the immune system and an increased burden of senescent cells with a secretory phenotype (SASP) [4546]. Support for the link between telomere length and systemic inflammation has recently been provided by the report that telomeric repeat-containing RNA (TERRA) is a component of extracellular inflammatory exosomes [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-126–3p inhibits endothelial inflammation, and low levels of miR-126–3p were found in patients with CVD and diabetes 50 , whereas miR-21–5p levels are correlated negatively with CRP and fibrinogen levels, and miR-21–5p levels are higher in patients with CVD than in age-matched controls 44 . Other miRNAs, such as miR-146 and miR-155, might also have a role in inflammageing by affecting cellular senescence or modulating immune responses, although these activities might not be reflected by changes in miRNA concentration or these miRNAs might be detected only in exosomes or other structures carrying miRNAs 51 . Overall, the contribution of miRNAs to inflammageing is an active area of investigation with high translational potential.…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%
“…Moreover, it was demonstrated that the functional hypothalamic stem/ progenitor cells release exosomes into the cerebral spinal fluid that likely contribute to slowing aging through transfer of miRNAs (57). Conversely, it has been demonstrated that senescent cells release more EVs and with a different composition (58)(59)(60), likely contributing to the SASP. Taken together, these results suggest that functional stem/ progenitor cell-derived EVs are able to extend healthspan and lifespan whereas senescent cell-derived EVs could function as pro-geronic factors.…”
Section: Evsmentioning
confidence: 99%